DIGITAL LIBRARIES: HISTORY AND MODERNITY - Умида Вахобова (Web of Journals Publishing, 2025)
The article examines the development of digital libraries from the first attempts at digital storage of information to modern global network resources. The article analyzes the stages of evolution of digital libraries, their role in transforming access to knowledge, as well as current trends, including open archives, digital collections and copyright issues.
Keywords: digital libraries, digitalization, access to information, digital collections, open archives, preservation of cultural heritage.